Analysis of The Influence of Customer Loyalty to GoFood Products in Indonesia - Budianto, Damis Veri; Pertiwi, Tri Kartika; Anwar, Muhadjir (Widya Cipta - Jurnal Sekretari dan Manajemen, 2023)
Loyalty is an effort to establish long-term relationships with customers. This study examines the effects of e-service quality and sales promotion on customer loyalty and satisfaction, considering satisfaction as a mediating variable in the context of GoFood products. The main objective of this research is to analyze the causal relationship between the independent variables and the dependent variable with the presence of intervening variables. The primary data source for this study is GoFood application users. Data was collected from a total of 327 customers across Indonesia who are GoFood users. The majority of GoFood customers in the sample are women (61%), have undergraduate education (56%), are students (50%), and have an income ranging from five hundred thousand rupiahs to one million one hundred thousand rupiahs (25%). The results obtained from this study are as follows: First, e-service quality contributes to customer satisfaction. Second, sales promotion contributes to customer satisfaction. Third, customer satisfaction contributes to customer loyalty. Fourth, e-service quality contributes to customer loyalty. Fifth, sales promotion contributes to customer loyalty. Sixth, sales promotion influences customer loyalty through the intermediary variable of satisfaction. Seventh, e-service quality influences customer loyalty through the intermediary variable of satisfaction.